Penggunaan Insulin dan Gliquidon pada Pasien Komplikasi Nefropati Diabetik Salah Satu Rumah Sakit di Lampung Tahun 2020 - Fernanda, Nia; Saputri, Gusti Ayu Rai; Ulfa, Ade Maria (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: Diabetic Nephropathy (DN) is major complication of diabetes mellitus (DM) which still become major health problem in Indonesia because the complications are short-term and long-term rational treatment requires patients with diabetes mellitus (DM) diabetic nephropathy (ND) complications to obtain treatment that suits the patient's circumstances and conditions which can be monitored with the 6T 1W indicator. Objective: To evaluate the rationality of antidiabetic prescription in DN outpatient from RS P Lampung. Methods: The design of this study was descriptive analytic to get the profil of the rational use of antidiabetic drugs. 49 participants were selected using inclusion and exclusion criteria. This study is non experimental which is analyzed descriptively by purposive sampling method. Restrospective data retrieval of the patient's medical records. The results of the study were compared to the (AAFP) American of Family Physicians, 2007 standard. Results: 95% of respondent diagnosed DN correctly based on the guideline. 58,1% of participants treated with insulin, whereas 39,2% got sulfonylurea. the antidiabetic drugs for ND outpatient in RS P Lampung were rationally prescribed based on the accurate diagnosis, appropriate medication, appropriate patients, precise timing of administration, appropriate way of administration and dose, and the alertness of side effects. Conclusion: The rational antidiabetic drugs for ND outpatient has been implemented in RS P Lampung.